Из истории наименований свидетелей в русском языке - Chashchina, Elena (Studia Rossica Posnaniensia, 2019)
The author in this research article analyses the names of witnesses in the period from Ancient Russia to the end of the 17th century. Vocabulary is analysed from the point of view of origin, semantics and sphere of usage. Russkaya Pravda (Rus’ Justice), birch bark manuscripts and business documents of the 15–17 centuries were used as research sources.